Anti-dandruff effects of butterfly pea flowers (Clitoria ternatea)-based shampoo: A pretest-posttest control study - Assegaf, Tengku SDIS.; Jusuf, Nelva K.; Pane, Yunita S.; Rusda, Muhammad; Darmani, Endang H.; Amin, Mustafa M.; Lubis, Ramona DS.; Bachtiar, Adang (Narra J, 2024)
Butterfly pea flower (Clitoria ternatea) may serve as an alternative anti-dandruff treatment; however, its effects on Malassezia spp. remain unexplored. The aim of this study was to explore the effects of C. ternatea as an herbal-based anti-dandruff treatment on Malassezia spp. DNA expression, plakoglobin levels, IL-8 levels, sebum levels, dandruff severity scores, adverse effects, and patient satisfaction. An experimental study with a pretest-posttest control design was conducted at Outpatient Clinic of Dermatology and Venereology, Arifin Achmad Hospital, Pekanbaru, Indonesia, from November 2023 to January 2024. The flower of C. ternatea was used to formulate the shampoo. The study involved 70 female patients aged 18–25 with dandruff, who were divided into two groups: (a) experimental group using 20% C. ternatea shampoo; and (b) control group using 2% ketoconazole shampoo. The present study found that 2% ketoconazole shampoo significantly reduced Malassezia spp. DNA expression compared to 20% C. ternatea shampooo (Clitoria ternatea: ΔCq=1.76±3.18; ketoconazole: ΔCq=3.77±2.90; p=0.008). No significant difference was observed in plakoglobin levels (C. ternatea: ΔCq=1.98±3.63; ketoconazole: ΔCq=2.50±2.36; p=0.427) or IL-8 levels (C. ternatea: ΔCq=3.46±4.00; ketoconazole: ΔCq=4.16 ± 3.62; p=0.459). C. ternatea significantly reduced sebum levels more than ketoconazole (C. ternatea: 1.16±0.98%; ketoconazole: 0.22±0.38%; p<0.001). Dandruff scores and patient satisfaction were similar for both shampoos (p=0.115 and p=0.336, respectively). Adverse effects were more common in the 2% ketoconazole shampoo group, affecting 21.2% of the patients. In conclusion, 2% ketoconazole shampoo is more effective in reducing Malassezia spp. DNA expression, while 20% C. ternatea shampoo offers better sebum control. Both shampoos are similarly effective in ameliorating dandruff severity and are well-tolerated, with fewer adverse effects reported for C. ternatea.